Dom Quentin's Memoir on the Text of the Vulgate - Rand, Edward Kennard (Harvard theological review, 1924)
In 1907, His Holiness, Pope Leo XIII appointed a Commission to revise and re-edit the text of St. Jerome's Latin version of the Bible, known as the Vulgate and accepted by the Roman Church as its standard text of Holy Scripture. The undertaking was assigned, most appropriately, to the Benedictine Order, which from the days of Cassiodorus to those of Mabillon and from Mabillon to the present time has a record of scholarly achievement that for depth and continuity no other organization, sacred or secular, can match. Far-reaching plans were formulated, and a veritable laboratory of textual research was established at the Benedictine monastery of St. Anselm on the Aventine. The methods employed for listing and assorting the manuscripts and for securing collations and photographs are described in two reports, entitled “The Revision of the Vulgate,” published at St. Anselm's in 1909 and 1911. The present writer had the pleasure of visiting the monastery in 1912, under the guidance of the learned Abbot, now Cardinal, Gasquet. An imposing amount of material had already at that time been collected, but the stupendous character of the undertaking hardly promised definite results, certainly not a final and authoritative text, within the limits of the present generation. And yet Dom Quentin, to whom the task of editing the text was assigned in 1907, has succeeded after nearly fifteen years of unremitting toil, in presenting a new survey of the history of the text of the Vulgate and a precise method for determining its original form.